A Study of the Possible Influence of the Criticism of Matthew Arnold upon the Critical Theories and Poetic Practice of Gerard Manley Hopkins - Stothart, Margaret (My University, 1972)
This thesis examines Hopkins's letters and journals in order to establish which of Arnold's works be read, and what he thought of them. It then compares Hopkins's critical theories, to be found in his letters, with those ideas of Arnold which Hopkins could have gleaned from his reading. A brief study of the poetry is made in the light of conclusions drawn in the earlier part of the thesis.
Keywords: English; English Language and Literature; English Language and Literature